2003
DOI: 10.1300/j013v38n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Women's Hysterectomy Experiences and Decision-Making

Abstract: The goal of the study was to examine women's experiences with gynaecologic symptoms and how they decided to undergo hysterectomy. For this purpose, twenty-nine women were interviewed in hospital within three days of undergoing hysterectomy. The interviews elicited information about the nature of the problem that caused the women to seek medical help, actions taken to solve their problem, their relationship with their gynaecologist, information seeking patterns and decision-making about hysterectomy. Although f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…It is the symbol of femininity, sexuality, fertility and motherhood in developing societies. 14,29 In our study, similar to the other conducted studies, the participants stated that they experience inability about their womanhood and motherhood roles. At the same time, it was identified that the women ex-International Journal of Hematology and Oncology perienced intense anxiety because of the inability in these roles.…”
Section: Discussionsupporting
confidence: 81%
“…It is the symbol of femininity, sexuality, fertility and motherhood in developing societies. 14,29 In our study, similar to the other conducted studies, the participants stated that they experience inability about their womanhood and motherhood roles. At the same time, it was identified that the women ex-International Journal of Hematology and Oncology perienced intense anxiety because of the inability in these roles.…”
Section: Discussionsupporting
confidence: 81%
“…A study of women's help-seeking decisions regarding hysterectomy demonstrates that most women rely on the advice of friends and family and have already decided on appropriate treatment before consulting a doctor (13). Support from others has been found to be a strong predictor of treatment seeking for urinary tract infections (14), mental health problems (15), brain tumors (16), and infertility (17).…”
Section: Determinants Of Help-seekingmentioning
confidence: 99%
“…); making treatment decisions about hysterectomies (Uskul et al . ); or managing homelessness (Reid et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, there was also potential for misinformation to be transmitted through trusted social contacts (Uskul et al . , Sutton et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation